Determining Ba isotopes of barite using the Na2CO3 exchange reaction and double-spike method by MC-ICP-MS. Issue 7 (24th May 2019) - Tian, Lan-Lan; Zeng, Zhen; Nan, Xiao-Yun; Yu, Hui-Min; Huang, Fang
Abstract : This study presents a practical method for high precision Ba isotope measurement of barite using a Na2 CO3 exchange reaction and 135 Ba– 136 Ba double-spike method by MC-ICP-MS. Abstract : This study presents a practical method for high precision Ba isotope measurement of barite using the Na2 CO3 exchange reaction and 135 Ba– 136 Ba double-spike method by MC-ICP-MS. The effects of matrices and conditions of the exchange reaction were rigorously examined. The precision and accuracy of this method were tested by measurement of a synthetic barite standard prepared by reacting Ba(NO3 )2 with Na2 SO4 . The δ 137/134 Ba of the synthetic barite is 0.06 ± 0.03‰ (2SD, n = 16) relative to SRM3104a, which is well consistent with the recommended value (0.07 ± 0.04‰, 2SD, n = 769). The robustness of this method was further assessed by replicate analyses of six barite reference materials, which cover a large range of BaSO4 contents from 18.87 wt% to nearly 100 wt%. The δ 137/134 Ba of pure barite international standard NBS127 is −0.21 ± 0.03‰ (2SD, n = 20); the δ 137/134 Ba of natural standards GBW07811, 07 812, 07 814, 07 815 and 07 816 is −0.06 ± 0.05‰ (2SD, n = 12), 0.24 ± 0.05‰ (2SD, n = 48), −0.02 ± 0.02‰ (2SD, n = 10), −0.05 ± 0.04‰ (2SD, n = 18), and −0.01 ± 0.05‰ (2SD, n = 20), respectively. Based on repeated analyses of these standards, the long-term external precision of δ 137/134 Ba is better than 0.05‰ (2SD), much smaller than the variation in these barite standards (up to 0.45‰), revealing the large Ba isotope fractionation in natural barites.